Subjectivity and Humanism as Two Major Factors of Jaun Paul Sartre’s Existentialism in: Gabriel Garcia Marquez’s ‘No One Writes to the Colonel’ - Harati, Maryam; Abadi, Mohammad Mahdi Kashani Lotf (Richtmann Publishing, 2011)
Existentialism, as the forerunner of twentieth centuryâ€™s thought schools, encompasses and gives far more meaning to theclassical work of literature even the most recent ones as Gabriel Garcia Marquez. It is one of the broad schools of thought and philosophythat deeply indebted to the ideas and studies of a French philosopher called Jean-Paul Sartre. â€œThe more fashionable a philosophybecomesâ€, Marjorie Grene states in his Introduction to Existentialism, â€œthe more elusive is its definitionâ€ (Grene 23). So, the proponentsof existentialism proclaim that though many attacks few understand them